Therapeutic Properties of Honey for the Management of Wounds; Is There a Role in the Armamentarium of Diabetic Foot Ulcer Treatment? Results From In vitro and In vivo Studies. (December 2021) - Anastasiou, Ioanna A.; Eleftheriadou, Ioanna; Tentolouris, Anastasios; Samakidou, Georgia; Papanas, Nikolaos; Tentolouris, Nikolaos
Diabetic foot ulcers are one of the most dreadful complications of diabetes mellitus and efforts to accelerate diabetic wound healing are of paramount importance to prevent ulcer infections and subsequent lower-limb amputations. There are several treatment approaches for the management of diabetic foot ulcers and honey seems to be a safe and cost-effective therapeutic approach on top of standard of care. The aim of this review was to summarize the therapeutic properties of honey and the data regarding its possible favorable effects on diabetic wound healing. A literature search of articles from 1986 until April 2021 was performed using MEDLINE, EMBASE, and the Cochrane Library to assess for studies examining the therapeutic wound healing properties of honey, it's in vitro effect, and the efficacy and/or mechanism of action of several types of honey used for the treatment of diabetic animal wounds. Honey has antioxidant, anti-inflammatory, and antibacterial properties and in vitro studies of keratinocytes and fibroblasts, as well as studies in diabetic animal models show that treatment with honey is associated with increased re-epithelialization and collagen production, higher wound contraction, and faster wound healing. The use of honey could be a promising approach for the management of diabetic foot ulcers.